The Cape Town Stereotactic pointer clinical development and Applications - Fieggen, Anthony Graham (Division of Neurosurgery, 2014)
This dissertation describes the development and clinical use of a novel stereotactic neurosurgical system, the Cape Town Stereotactic Pointer (CTSP). This system has four main components; a halo containing three fiducials also serves as the platform for a tripod pointing device which is set with the aid of a 3D phantom or a printed setting diagram, and software which enables transformation of imaging space into patient space. Laboratory tests indicated an application accuracy of 1.9 +/- 0.6mm using the 3D phantom to set the tripod. From the first clinical application, the system underwent a series of iterations which could broadly be divided into four successive phases of refinement. This took place over a six year period, encompassing one hundred patients who underwent 115 stereotactic procedures. Indications for surgery included biopsy (62.6%), aspiration (15.7%) and cannulation (21.7%) and the surgical objective was realized in 101/109 cases (92.7%). Given the fact that six of the eight failures represented errors of surgical judgment that could not be ascribed to the device, and each of two system errors resulted in a significant modification to the system, the CTSP demonstrated a satisfactory level of accuracy in the clinical setting. This was accomplished at an acceptable complication rate, with one death five days after surgery attributable to a stereotactic procedure (mortality 0.9%) and major morbidity in two cases (1.7%); thirteen patients experienced minor complications, all of which proved to be transient (11.3%). A simple protocol for use of the CTSP evolved over the course of this study, making it easier for neurosurgeons from varying backgrounds to introduce stereotaxis into their practice with the help of this system. In addition to satisfactory levels of clinical reliability and safety, the system was versatile and also well tolerated by patients. It is hoped that the CTSP provides a costeffective alternative for neurosurgeons working in under-resourced settings. Sixty units of the production version of the CTSP have been sold and the system is now in use in ten countries.